2017
DOI: 10.1101/192369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reconstructing the Molecular Life History of Gliomas

Abstract: 10At the time of clinical presentation, the very heterogeneous group of pediatric and adult gliomas carry a 11 wide range of diverse somatic genomic alterations. These include chromosome-sized gains and losses, 18 pathway and the acquisition of a telomere maintenance mechanism can bypass these bottlenecks. We 19 relate somatic alterations to each of these steps, in order to reconstruct the life history of glioma. 20Understanding the story that each glioma tells at presentation may facilitate the design of nove… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 234 publications
(204 reference statements)
0
15
0
Order By: Relevance
“…Gliomas are the largest group of intrinsic brain tumours with age adjusted incidence rates ranging from 4.67 to 5.73 per 100,000, causing more years of life lost compared with other cancers [1,2]. Glioblastoma (GBM) is the most malignant glioma and is classified molecularly as IDH-wildtype and IDH-mutant GBM [3][4][5][6][7][8][9][10]. During gliomagenesis, an array of genetic alterations may cause the dysregulation of cell growth signalling and cell cycle pathways [6,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gliomas are the largest group of intrinsic brain tumours with age adjusted incidence rates ranging from 4.67 to 5.73 per 100,000, causing more years of life lost compared with other cancers [1,2]. Glioblastoma (GBM) is the most malignant glioma and is classified molecularly as IDH-wildtype and IDH-mutant GBM [3][4][5][6][7][8][9][10]. During gliomagenesis, an array of genetic alterations may cause the dysregulation of cell growth signalling and cell cycle pathways [6,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Neural stem cells in the subventricular zone may harbour recurrent driver somatic mutations that are shared with the tumour bulk (e.g., P53, PTEN, EGFR, and TERT) [17]. Telomerase (reactivation or reexpression) can occur in IDH wildtype and mutant GBMs driven either by telomerase reverse transcriptase (TERT) promoter mutations or other mechanisms [8,18]. e current standard-of-care for glioblastomas remains as maximal safe surgical resection with concurrent radiotherapy and temozolomide (TMZ) chemotherapy (Stupp protocol) [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Within the same patient, though different subtypes of cells shared many commonalities in CNV changes and regulon network, there were differences to some degree. We found that the non‐GSCs, which shared more common features in CNV or regulon network with a specific GSC, were derived from this GSC by trajectory analysis, suggesting that the differentiation or evolution of tumor cells is a gradual process with mutation accumulation 26 . We also identified the subclones of the same subtype in the same patient.…”
Section: Discussionmentioning
confidence: 78%
“…It indicated that some subclones were less affected by inter‐tumoral heterogeneity and we speculated that these subclones may be directly derived from driver mutations 30,31 . In patient BT_S4, ME_2 showed a tendency of transition to ME_1 subclones, and we thought that these two subclones possessed the same progenitor and were at different phases of glioma genesis of one consecutive evolution process 26 …”
Section: Discussionmentioning
confidence: 85%
“…The tumorprivate mutations in the tumor tissue might facilitate the development of a new targeted therapy. In addition, the anatomical location of those cells would mature the Big Bang theory 7,60) into the Firework theory of subventricular abnormal cells 43) .…”
Section: History : Progress Toward the Stem Cell Origin Of Gbmmentioning
confidence: 99%